RND Efflux Systems Contribute to Resistance and Virulence of Aliarcobacter butzleri - Mateus, Cristiana (2022)
(This article belongs to the Special Issue The Structural and Functional Study of Efflux Pumps Belonging to the RND Transporters Family from Gram-Negative Bacteria)